PREVALENCE OF CAFFEINE INTAKE AMONG MEDICAL STUDENTS AND FACTORS ASSOCIATED WITH IT (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Caffeine is one of psychoactive substances in the world and it is taken as coffee, tea, energy drinks etc. The adverse effects of caffeine range from mild to severe and generally go unnoticed by an individual. Medical student’s life begins with regular exam preparation. Medical students have to put forth extra effort beyond their mental threshold and physical stress to show progress in their exams. Increased stress status among medical students promotes the use of caffeine. The study was postulated in order to know the reasons, circumstances under which students consume caffeine and the symptoms that they face due to caffeine consumption. Objectives 1.    To assess the prevalence of Caffeine intake among medical students. 2.    To identify the factors associated with the intake of Caffeine among the medical students Methods: A cross sectional study was conducted among the medical college students. A total of 140 students participated in the study. Prevalence of caffeine consumption was assessed using a pretested semi structured questionnaire. Results: Among the 140 students, about 112 (80%) were caffeine consumers and 28 (20%) did not consume caffeine. The type of caffeine product consumed varied from Coffee/ Tea (83%), Energy drinks (7.1%) and Soft drinks (9.8). Among 112 students, 77 (68.75%) of students consumed caffeine due to stress during exams and second reason for caffeine consumption in 69 (61.61%) students was to say alert. 107 (95.54%) of consumers fall into the low- moderate intakers category, consuming less than 3 cups of caffeine per dayand only 5 (4.46%) consumed more than 3 cups per day. Conclusions: Although moderate caffeine intake is generally safe, its overuse among medical students could have led to adverse health outcomes, including sleep disturbances, anxiety, and increased stress. It is essential to encourage healthy lifestyle practices, stress and time management and also to reduce reliance on caffeine.